Visual assessment of viewing direction based on color discrimination. Issue 4 (2nd October 2019) - Kim, Moon-Cheol
Abstract : For the large-screen TV viewer, it makes sense to obtain visual information within the same viewing direction rather than based on any physical change between the normal-axis and viewing directions, as in the conventional measurement methods. The aim of the proposed visual assessment method is to enable visual assessment based on color discrimination. This article describes a structural sensitivity assessment method that is dependent on the viewing direction, interpretation of the assessment results, and correlation between the assessment and S-CIELAB results. The paper also reviews the impacts of the color changes, image complexities, and image luminance of the test patterns on the visual assessment results. In fact, the proposed method has a good correlation with the S-CIELAB method. It may be used in the display industry as a supplemental method to physical measurement.